1994
DOI: 10.1002/syn.890180408
|View full text |Cite
|
Sign up to set email alerts
|

Quantal analysis of presynaptic inhibition, low [Ca2+]0, and high pressure interactions at crustacean excitatory synapses

Abstract: The cellular mechanisms underlying the effects of high pressure, GABAergic presynaptic inhibition, and low [Ca2+]0 on glutamatergic excitatory synaptic transmission were studied in the opener muscle of the lobster walking leg. Excitatory postsynaptic currents (EPSCs) were recorded with or without prior stimulation of the inhibitor using a loose macropatch clamp technique at atmospheric pressure and at 6.9 MPA helium pressure. High pressure reduced the mean EPSC amplitude and variance, decreased the quantal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Bykhovskaia et al, 1999;Bykhovskaia et al, 2004;Golan et al, 1994;Golan et al, 1996;Goy and Kravitz, 1989;Grossman and Kendig, 1990;Kravitz et al, 1980;Vorob'eva et al, 1999;Worden et al, 1997;Worden and Camacho, 2006;Worden et al, 1995). The composition of this saline is based on a 'perfusing solution' that Cole developed more than 60 years ago by comparing a series of solutions with varying concentrations of sodium, potassium, calcium, magnesium and sulfate to determine which was the optimal mixture for maintaining the strength and frequency of the lobster heartbeat in vitro at 17°C (Cole, 1941).…”
Section: The Temperature Dependence Of Hemolymph Phmentioning
confidence: 99%
“…Bykhovskaia et al, 1999;Bykhovskaia et al, 2004;Golan et al, 1994;Golan et al, 1996;Goy and Kravitz, 1989;Grossman and Kendig, 1990;Kravitz et al, 1980;Vorob'eva et al, 1999;Worden et al, 1997;Worden and Camacho, 2006;Worden et al, 1995). The composition of this saline is based on a 'perfusing solution' that Cole developed more than 60 years ago by comparing a series of solutions with varying concentrations of sodium, potassium, calcium, magnesium and sulfate to determine which was the optimal mixture for maintaining the strength and frequency of the lobster heartbeat in vitro at 17°C (Cole, 1941).…”
Section: The Temperature Dependence Of Hemolymph Phmentioning
confidence: 99%
“…The threshold pressure for HPNS is variable and affected by the rate of compression (18). Details regarding the cellular mechanism(s) underlying HPNS are unclear (114), but it appears that both synaptic (74,76,85,228,229) and intrinsic membrane properties are involved (72,73,191,192,216). Several excellent reviews on HPNS exist elsewhere (18,100,104,114).…”
Section: Hydrostatic Compression Of the Brainmentioning
confidence: 99%
“…Indeed, it has previously been shown that synaptic transmission is suppressed by HP whether in vertebrate CNS synapse (Parmentier et al, 1981; Schleifstein-Attias et al, 1994), squid giant synapse (Parmentier et al, 1981), or crustacean neuromuscular junction (NMJ) (Campenot, 1975; Grossman and Kendig, 1990), either in excitatory (Grossman and Kendig, 1988; Golan et al, 1994) or inhibitory (Golan et al, 1994) synapses. Postsynaptic reduction in receptor sensitivity, observed in glycine receptors (Shelton et al, 1993), will exacerbate pressure-induced suppression in specific synapses (Daniels and Grossman, 2003).…”
Section: Introductionmentioning
confidence: 99%